2004
DOI: 10.1002/ijc.20056
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer cells induce osteoclast formation by stimulating host IL‐11 production and downregulating granulocyte/macrophage colony‐stimulating factor

Abstract: Breast cancer cells frequently metastasize to the skeleton, where they induce OCL formation and activity, resulting in extensive bone destruction. However, the mechanisms by which breast cancer cells mediate increased osteolysis remain unclear. To elucidate this point, we investigated how 3 human breast cancer cell lines, MDA-MB-231, MDA-MB-435 and MCF-7, induce OCL formation using a murine osteoblast-spleen cell coculture system and compared their effects with a human colorectal cancer cell line, HCT-15; a hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…It is important to note that IL-11 (and CTGF) can only be considered candidate bone metastasis genes at present. IL-11 is known to stimulate osteoclastic bone resorption in vitro (27)(28)(29), but it has complex effects on bone formation, including positive effects (37). Its role as a mediator of bone metastasis in humans remains to be established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that IL-11 (and CTGF) can only be considered candidate bone metastasis genes at present. IL-11 is known to stimulate osteoclastic bone resorption in vitro (27)(28)(29), but it has complex effects on bone formation, including positive effects (37). Its role as a mediator of bone metastasis in humans remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…We recently identified a set of genes that mediate osteolytic bone metastasis by MDA-MB-231 cells (17). Among these genes, IL-11 was of interest because it has been proposed to play a role in osteoclast differentiation (27) and as a mediator of osteolysis in breast cancer bone metastasis (28,29). Enforced expression of IL-11 in MDA-MB-231 cells increases their bone-metastatic activity (17).…”
Section: Smad4-dependent Transcriptional Activation Of Candidate Metamentioning
confidence: 99%
“…A number of studies proved that IL-11, as a cytokine with multi-biological effects, when specifically bound with the α-chain of its receptor, becomes a complex with high affinity for the intermembrane signal transduction glycoprotein 130. The complex activates the Jak-STAT signal pathway and facilitates the phosphorylation of p-hydroxyphenylalanine kinase, thus exerting related biological effects (6,13,14). Using phage display peptide library screening technology, it was revealed that the nonapeptide c(CGRRAGGSC), as an analog of IL-11, is able to specificically target to the prostate tumor.…”
Section: A B Discussionmentioning
confidence: 99%
“…We chose to investigate the effect of COX-2 in breast cancer metastasis to bone because (1) COX-2 is expressed in poor-prognosis human breast cancers including those overexpressing HER2 and (2) studies with cell lines and mouse models indicate that COX-2 overexpression in breast cancer cells inhibits apoptosis of breast cancer cells and promotes metastasis (Liu et al, 2001;Basu et al, 2004;Singh et al, 2005). Other in vitro studies have shown that breast cancer cells can stimulate osteoblasts and stromal cells to produce PGE 2 , which in turn induces osteoclastogenesis thus causing osteolytic bone metastasis (Ono et al, 2002;Morgan et al, 2004). Our cumulative evidence for the role of COX-2 in bone metastasis is based upon: (1) increased bone metastasis upon COX-2 transfection of breast cancer cells (Figure 1), (2) inhibition of bone metastasis (in both prevention and treatment regimens) by MFtricyclic (Figures 3 and 4) and (3) demonstration that BSCs of breast cancer cells produce higher levels of PGE 2 than the parental cell population (Figure 2), perhaps reflecting that PGE 2 confers an advantage on breast cancer cells for bone metastasis.…”
Section: Discussionmentioning
confidence: 99%